A palynological investigation of some taxa of the genus Ranunculus L. (Ranunculaceae) in Turkey and its taxonomic value - Kursat, Murat; Ozdag, Neriman; Baser, Birol; Ozbey, Fahrettin; Emre, Irfan (Taylor & Francis Inc, 2022)
Ranunculus L. (Ranunculaceae) is morphologically very diverse and palynological characters support the systematic studies of the genus. This study was aimed to perform palynological investigations of 30 different taxa of Ranunculus by using light microscope (LM) and scanning electron microscopy (SEM) methods. Polar-equatorial axis measurements, exine-intine layer thicknesses and colpi-pori numbers of pollen grains were examined using the Wodehouse method. Surface ornamentations were determined by electron microscope. The dendrogram of palynological characters analysed on the LM and SEM and observations made by multi-variate statistical package software partly support the monophyletic genera. According to the palynological dendrogram, Ranunculus taxa are divided into three types and R. arvensis clustered only in type 2. The results from present study suggest that the palynological characters can be useful for clarifying the taxonomic relationship in the genus.
Keywords: Pollen; Ranunculus L.; scanning electron microscope (SEM); taxonomy